Supermarket and media audit of health messages relating to seafood - Nicholson, Claire; McManus, Alexandra; Fielder, Lynda (Centre of Excellence Science Seafood & Health (CESSH), 2009)
A supermarket audit was conducted to observe any health messages available to consumers that were being displayed near seafood products. Other messages displayed near seafood and other foods were also recorded.Forty three retailers were visited during January of 2009. In addition, a brief media scan covering the six months leading up to the audit was also conducted to identify other seafood related health messages that consumers were exposed to.Key findings from the audit included: -Of the 43 retailers visited, 13 (30%) displayed some kind of healthmessage. -Twenty health messages were identified. -Half of the messages (n=10) described specific benefits of seafood or fish consumption. -Most retailers (91%) displayed some kind of non-health related message near seafood products. -Meat products were linked to barbeques and Australia Day more often than seafood; however seafood was linked to health more often than meat or poultry products. -Fish oil products promoted the specific benefits of Omega 3 intake. -Media articles contain information on the health benefits of seafood, but this information was sometimes conflicting or confusing.